Kinerja Rangkak pada Balok Beton Sandwich dengan Isian Styrofoam (Cement EPS Sandwich Panel) - Rilo Hanif Hasbi Ardin; Yohanna Ariesta; Rr. M.I. Retno Susilorini; David Widianto Widianto (G-SMART, 2017)
Precast material is a user-friendly construction product. One innovation that is being developed is sandwich concrete. Sandwich concrete is composed by skin layers, that are strong and stiff, and lightweight concrete as core layer. As a part of builiding construction, each structural and non-structural element resists load in certain time. The purpose of this research is to investigate creep performance of concrete sandwich beam. By observing the effect of creep, it can be known the long-term effect due to the constant loading on a material. The test specimen is formed of sandwich construction beam, with its core layer consists of lightweight concrete and styrofoam (cement EPS sandwich panel) mixture. This research conducted with two kinds of size and proportions of specimen, single beam (length=100 cm; width=20 cm; thickness=7,5 cm)and double beam (length=100 cm; width=20 cm; thickness=7,5 cm)which is a combination of single beams glued together with Sikabond. The loading method that used in this research is third point loading as described on ASTM C393 in two positions, horizontally and vertically. After having loaded of 3 kN in 2 hours, each test specimen has deflected and gives creep strain value. The values of creep strain are: specimen RH-S01 by 3,23%, specimen RV-S03 by 0,40%, specimen RH-D03 by 0,60%, dan specimen RV-D02 by 0,32%.The smallest value of creep strain obtained by double beam that was tested vertically, due to have greater EI value than the horizontally tested specimens. According to the maximum deflection and load that can be resisted by the specimens, sandwich concrete shall not be recommended for structural beam. This research shows that the creep effect of constant loading by 3 kN for 2 hours on sandwich concrete beam is not secure